Knowledge and Practice of Impression Techniques for Complete Edentulous Patients - J. APARNA,; MAITI, DR. SUBHABRATA; BRUNDHA, DR. MP.; P, DR. JESSY. (The journal of contemporary issues in business and government, 2020)
Impression making for completely edentulous patients is one of the critical factors in determining the success or failure of complete denture therapy. Precise reproduction of an edentulous foundation is essential for removable prosthesis retention, stability, and support. Evidence indicates that materials and methods differ in the way impressions are produced for complete dentures. An online survey involving 100 individuals by random sampling method which included Prosthodontics Postgraduates, Undergraduates, and General Practitioners from different locations in India after getting proper consent from the participants about various impression techniques performed for completely edentulous patients. The results were collected and then analyzed through SPSS software. Descriptive statistical analysis was carried out and the chi-square test was used and the p-value was calculated. This survey analysis has provided a clear view about the impression techniques and practices followed by Dental Practitioners in the process of taking an impression for completely edentulous patients which included theory followed during impression making, primary impression-tray, border molding material, primary and final impression material, border molding material, correction material, use of the custom tray, tissue stop, spacer, posterior palatal seal, flabby tissue and neutral zone for the taking of better impressions for completely edentulous patients. The present study about the knowledge and practice of impression techniques followed by Indian Dental Practitioners has provided a clear view about the current procedures undertaken by them and also provides a better view to improving certain procedures and techniques for the betterment of patients in future